Chinese export porcelain in the middle Qing Dynasty: Study on the blue-and-white porcelains excavated from the "Xiaobaijiao I" shipwreck. (August 2021) - He, Yan; Li, Weidong; Lu, Xiaoke; Xu, Changsong; Jin, Tao; Lin, Guocong
Highlights: The raw materials with different quality were used for two type of porcelain wares. Kaolin was added into pigment batch for blue-and-white porcelain. The spinel-structured CoAl2 O4 is conducive to the color of the underglaze patterns. The clarity of pattern is affected by many anorthite and quartz grains in glaze. The exported porcelain still maintained high quality in the middle Qing Dynasty. Abstract: The "Xiaobaijiao I" shipwreck of the Daoguang period (1821–1850 CE) of the Qing Dynasty (1636–1912 CE) was found in the sea area of North Yushan Islands of China, from which a total of 592 blue-and-white porcelain wares were excavated. These precious cultural relics and shipwreck itself are powerful witnesses of the Maritime Silk Road. In this study, energy-dispersive X-ray fluorescence was used to analyze the body and glaze compositions of the typical blue-and-white porcelains from the shipwreck. Based on the differences in trace elements such as Rb, Zr, and Mn, the two types of blue-and-white porcelains from different origins can be distinguished. X-ray diffraction analysis and scanning electron microscope show that there are only a few unmelted quartz grains in the glaze of type 1, while type 2 has a lot of sub-micron to micron-sized anorthite crystals within the glaze layer owing to the firing temperature being lower than that required for a proper firing. Thus the strong light scattering effect upon the incident light caused by anorthite and quartz crystals seriously reduces the transparency of the glaze layer and results in the underglaze blue patterns to appear dull and unclear. Combining the results of energy-dispersive X-ray fluorescence and micro-Raman spectroscopy, pigment particles at the glaze-body interface of the first type mainly exist in the form of spinel-structured CoAl2 O4 and its solid solutions, which is associated with the pre-processing of the pigment. The clarity and sharpness of the underglaze blue patterns come from the excellent thermal stability of the spinels consisting of the pigment. While the blurred effect of the underglaze blue patterns of type 2 is mainly due to Co 2+ ions partially melting into the glaze at high temperature and coloring the glass phase. The study on "Xiaobaijiao I" shipwreck and the porcelains it carried can reflect the overview of the Chinese porcelain production and exportation in the middle Qing Dynasty.